Isolation and Identification of Pathogenic Fungi from Cyprinus carpio L. (1758) in Al-Nasiriya City - Ihsan Flayyih Hasan AI-Jawhari (Journal of Global Pharma Technology, 2016)
Thirty samples of Cyprinus carpio were collected from Al-Nasiriya fish ponds during the period from March until Novmber 2017 . Seventeen fish samples showed fungal infection .In this study eight species were identified and the most common were Aspergillus niger, Saplolegnia sp., Achyla prolifera, Alternaria alternate , Penicillium funigulosum, Rhizopus stolinifer, Aspergillus fumigatus and Aspergillus flavus . Aspergillus Niger and Saplolegnia sp. were the most prevalent fungi infecting all the organs of Cyprinus carpio. Gills and abdomen had higher infection than rest of the organs .Keywords: Contaminnet, Disease, Environment, Fishes, Fungi, Ponds.